Ketogenic Diet Therapy for the Treatment of Post-encephalitic and Autoimmune-Associated Epilepsies - Husari, Khalil S.; Cervenka, Mackenzie C. (Frontiers in Neurology, 2021)
Introduction: Acute Encephalitis is associated with a high risk of acute symptomatic seizures, status epilepticus (SE), and remote symptomatic epilepsy. Ketogenic diet therapies (KDT) have been established as a feasible and safe adjunctive management of refractory- and super-refractory SE. However, the role of KDT in the chronic management of post-encephalitic epilepsy (PE) and autoimmune-associated epilepsy (AE) is unknown. This study aims to investigate the use of KDT in patients with PE and AE. Methods: A retrospective single-center case series examining adult patients with PE and AE treated with the modified Atkins diet (MAD). Results: Ten patients with PE and AE who were treated with adjunctive MAD were included. Four patients had either confirmed or presumed viral encephalitis, 5 patients had seronegative AE, and 1 patient had GAD65 AE. The median latency between starting MAD and onset of encephalitis was 6 years (IQR 1-10). The median duration of MAD was 10 months (IQR 3.75-36). Three patients (30%) became seizure-free, 1 patient (10%) achieved 90% seizure freedom, and 3 patients (30%) achieved a 50-75% reduction in their baseline seizure frequency, while 3 patients (30%) had no significant benefit. Overall, 7 patients (70%) achieved ≥ 50% seizure reduction. Conclusion: In addition to its established role in the treatment of RSE, KDT may be a safe and feasible option for the treatment of chronic PE and AE, particularly in those with prior history of SE. Prospective studies are warranted to explore the efficacy of KDT in management of patients with PE and AE.